Hydrogeological mapping of heterogeneous and multi-layered ophiolitic aquifers (Mountain Prinzera, northern Apennines, Italy). Issue 2 (30th November 2017) - Segadelli, Stefano; Vescovi, Paolo; Chelli, Alessandro; Petrella, Emma; De Nardo, Maria Teresa; Gargini, Alessandro; Celico, Fulvio
ABSTRACT: A few hydrogeological studies have been carried out worldwide in peridotite aquifer systems, despite their wide distribution. The ophiolites are one of the main groundwater reservoir within the northern Apennines (Italy). This paper suggests the graphical solution to set the hydrogeological map of heterogeneous, multi-layered ophiolitic aquifers mapped on large scale (1:1600). The site investigation area is an ophiolite outcrop of the External Ligurian of the northern Apennines: the Mountain Prinzera rock complex area (44°38′30″N, 10°5′E; Parma Province, Emilia-Romagna Region). The hydrogeological characteristics of the tested aquifer system do not allow setting a hydrogeological map by applying usual graphical approaches. The hydrogeological map in such complex aquifer systems will show the classic hydrogeological data but must put in evidence above all (i) the main heterogeneities of the system, from the hydraulic point of view and (ii) the modifications of groundwater scenarios and pathways over time. The hydrogeological database of Mt Prinzera aquifer was managed in ESRI ArcGIS 10.0 software.